ASEAN and Transnational Crime: Gains and Challenges in Tackling Drug Trafficking - Yang, Mok Shen Yang (WIMAYA, 2020)
This essay discusses the drug problem in ASEAN, how the drug problem in the region has been securitized, and the challenges faced by ASEAN in implementing effective solutions. ASEAN is home to the Golden Triangle, an area that is located where the borders of eastern Myanmar, north-western Lao PDR and northern Thailand converge along the Mekong River and infamously known as one of the world’s leading regions for narcotics production. To understand the drug problem in ASEAN, one has to approach it from various perspectives that look beyond just the criminality of drug trafficking and the production and consumption of illicit drugs. This article will therefore argue that despite the constant reiteration of the need to tackle the issue of drug trafficking, the ASEAN mechanism has not been able to effectively address the multifaceted nature of illicit drugs in the region due to limitations posed by the “ASEAN Way”.